Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Stad (Student Teams Achievement Division) Pada Konsep Usaha Dan Energi Kelas Viii Smp Negeri 1 Jawilan - Yaohari, Holid Tantowi (Gema Widyakarya bekerjasama dengan Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2018)
The purpose of this classroom action research is to improve students' learning outcomes through efforts to improve the learning process that has been going on using STAD (Student Teams Achievement Division) learning model on business and energy concept of VIII SMPN Negeri 1 Jawilan Serang. This classroom action research is conducted in 2 cycles, each cycle in the research includes 4 steps, namely (1) planning (planning) which includes identifying the problem and determining the root cause of the problem; (2) execution (acting), implementing action in the form of learning business and energy concept by applying STAD learning model; (3) observation (observing), collecting data to determine the effectiveness of the action undertaken; (4) reflecting, analyzing the data and reflecting on it through the changes that occurred during the study. Implementation of research consisting of 2 cycles is obtained results that in cycle 1 student learn 63% complete with average value 70. Cycle 2 has increased student learning 84% complete with an average of 77. Of the 2 cycles undertaken students are more motivated to learn and prefer the class condition at the time of learning as disclosed by students in the questionnaire and interview. Research conducted during this 2 cycles obtained the result that learning by applying STAD learning model on cycle 2 has a positive effect on the effort to improve student learning result in effort and energy concept. This is evidenced from preliminary data obtained before the study of the average value of daily re-examination of 60 students to 77 with learning completeness of the original 50% to 84%.